Responders vs Non-responders to Cardiac Resynchronization Therapy: A Review Article - Aris Munandar Zulkifli Ismail; Ardian Rizal; Heny Martini; Novi Kurnianingsih (Universitas Brawijaya, 2020)
More than two decades after the introduction of cardiac resynchronization therapy (CRT) into clinical practice, respond to highly effective treatments for refractory drug heart failure (HF) approximately one-third of candidates persist to fail. This article will discuss indications for initiating a CRT, the definition of a response to a CRT, steps in response to a CRT, predictors of a CRT response, clinical judgment of patients who do not respond to CRTs, and elimination for possible reversible non-response causes. Here we have reviewed non-response CRTs in many ways. In short, multidisciplinary efforts are needed to overcome them because of the multifactorial causes of non-response (NR). So far, several factors has slowed the progress, such as limitations of NR consensus definitions and technology for therapeutic delivery.Keywords: Cardiac Resynchronization Therapy, Responder, Non-responder